Bonifacio ang unang pangulo - Williams, Enzo (Tuko Film productions, Inc., 2014)
Bonifacio: ang unang pangulo is a historical action epic that brings to light the true to life story of Philippine National hero, Andres Bonifacio, with his virtues and umanity, unfolding through the eyes of a high school student.